Mathematical Topology Meets Tradition: Alexander Polynomial Analysis of Sidalungguh Ketupat Weaving Patterns - Ja'faruddin, Ja'faruddin (Universitas Cokroaminoto Palopo, 2025)
This research aims to describe the relationship between mathematics and culinary culture, specifically focusing on ketupat, particularly the Sidalungguh Ketupat. Using knot theory applications, this study examines how mathematics and culinary culture are interconnected. This analysis was conducted by comparing the knots in the ketupat with knot theory literature, leading to the creation of knot diagrams. Through identification using Alexander polynomials, the following result was obtained: This research was conducted to explore the scientific potential in examining mathematics through traditional food. This research aims to describe the relationship between mathematics and culinary culture, specifically focusing on ketupat, particularly the Sidalungguh Ketupat. Using knot theory applications, this study examines how mathematics and culinary culture are interconnected. This analysis was conducted by comparing the knots in the ketupat with knot theory literature, leading to the creation of knot diagrams. Through identification using Alexander polynomials, the following result was obtained: This research was conducted to explore the scientific potential in examining mathematics through traditional food.